Antecedents of entrepreneurial intention among university students - Indiani, Ni Luh Putu; Sontong, Mariani Seti (International research journal of management, IT and social sciences, 2023)
The number of entrepreneurs in Indonesia is still lagging behind several other countries. This shows a lack of entrepreneurship intention among youth. This research was conducted based on the gap in the results of previous research and differences in the focus of discussion on several factors that affect the entrepreneurial intention of university students. This study analyzes and determines the effect of motivation, family environment, entrepreneurship education, and income expectations on student entrepreneurship intention. This study’s population was all university students in Bali, with a research sample of 250 respondents. Data were analyzed using multiple linear regression. The results showed that motivation, family environment, entrepreneurship education, and income expectations positively and significantly influenced student entrepreneurship intention. To increase motivation, students must believe that entrepreneurship can deliver the desired standard of living. To improve the family environment, students must feel their parents will always support and help them in entrepreneurship. To increase income expectations, students must be sure that by becoming an entrepreneur, they will earn greater and even unlimited income than being an employee. Aspects that need to be considered to improve entrepreneurship education are that students must take entrepreneurship courses, seminars, and entrepreneurship education well.